IMPLEMENTATION OF CRITIC METHOD AND MAUT METHOD FOR TEACHER PERFORMANCE EVALUATION SMP SWASTA BABUL ULUM - Murdani; Lince Tomoria Sianturi (INFOKUM, 2022)
In the world of education, teaching activities are the most important thing both at school and at the university.The role of the teacher as a teacher in the teaching and learning process is very important. Teachers as educators who become teachers, mentors, coaches in teaching and learning activities both at school and at the university. A teacher who is said to be professional must have a commitment to students. SMP SWASTA BABUL ULUM is one of the educational units in Darul Aman, Kec. Longkib, Subulussalam City, Aceh. In carrying out its activities, Babul Ulum Private Junior High School is under the auspices of the Ministry of Education and Culture. The principal is the leader in the school. As a school principal, he must be able to regulate and direct teachers to carry out quality education. Teacher performance evaluation aims to determine the quality level of teachers in SMP SWASTA BABUL ULUM . The ongoing teacher performance evaluation system is still carried out subjectively, because there are no aspects of assessment used in evaluating teacher performance in schools SMP SWASTA BABUL ULUM.To overcome these problems, it is necessary to apply decision making using the CRITIC Method and MAUT Method for evaluating teacher performance on SMP SWASTA BABUL ULUM so that the teacher performance evaluation system is no longer carried out subjectively.